Impact of tariff reduction on exports: A quantitative assessment of Indian exports to US - Aradhna Aggarwal (Indian Council for Research on International Economic Relations (ICRIER), 2004)
This paper quantitatively assesses likely changes in market access opportunities for Indian exports owing to tariff reductions by the USA. The study identifies particular products for India at the ISIC 4-digit level of disaggregation, which could be considered tariff sensitive. Regression analysis of the relationship between MFN tariff rates and India's exports to the US was used to assess in quantitative terms the likely impact of tariff reduction that may be agreed in the Doha Round. This analysis suggests that tariff cuts are not expected to benefit India's exports to the US in a major way. With the full implementation of the Chairman's formula for tariff cuts, increase in India's exports to the US would amount to 1.2 or 0.6 depending on the value of the B coefficient in theChairman's formula. These findings are in all likelihood substantially due to the tariff diversion effect of NAFTA preferences in favour of suppliers in Mexico, which is a competing country in many traditional items. It is expected that reduction of MFN tariff would alleviate the trade diversion effect of the NAFTA.The study has also attempted to decompose changes in India's total exports due to tariff reductions in the US into the competitive and market effects. The analysis suggests that the increase in India's exports would be mainly due to the competitive effect. This leads the author to conclude that it is crucial for India to improve its competitiveness vis-a-vis its competitors in different markets.
Keywords: 330; Zollpolitik; Export; Internationaler Wettbewerb; Indien; USA